2016
DOI: 10.1016/j.athoracsur.2015.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplant With Cardiopulmonary Bypass: Impact of Blood Transfusion on Rejection, Function, and Late Mortality

Abstract: All blood products administration regardless of amount transfused did not appear to affect early rejection outcomes or forced expiratory volume in 1 second expressed as percentage of forced vital capacity at 3 and 6 months. Use of RBC and FFP had no effect on survival. However, greater platelet usage appeared to adversely affect early but not late mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…The effect of RBC transfusion on long-term graft function and overall mortality, however, is less clear. One retrospective single-center study of 134 patients by Weber et al 20 found that transfusion of >4 U RBCs was associated with increased 1-year mortality, while larger studies by Ong et al 21,22 found no significant difference in 3-and Figure 1. Blood product transfusion in the peritransplant period and associations with adverse outcomes.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%
“…The effect of RBC transfusion on long-term graft function and overall mortality, however, is less clear. One retrospective single-center study of 134 patients by Weber et al 20 found that transfusion of >4 U RBCs was associated with increased 1-year mortality, while larger studies by Ong et al 21,22 found no significant difference in 3-and Figure 1. Blood product transfusion in the peritransplant period and associations with adverse outcomes.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%
“…While preoperative transfusion of PRBC in patients awaiting lung transplantation had been connected to reduced survival after lung transplantation by other investigators before, 27 intraoperative allogenic blood transfusion was found to have no undesirable impact on outcome among 310 lung transplantation recipients. 28,29 The risk for developing transfusion reactions might even be attenuated in this population, which could be due to suppression of immunological reactions by transfusion of irradiated PRBC and perioperative immunosuppression. 30 Additionally, in a recent study with 833 patients undergoing heart transplantation only transfusions exceeding six units of PRBC have been linked to worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Ong et al 52 in their retrospective study showed that PGD-related mortality and 1-year mortality were increased in LTX recipients (n = 311 over a period of 10 years) who had received >1 unit of platelet transfusion in the 24-hour perioperative period. Red cell transfusion and plasma infusion were not associated with increased PGD, mortality, or worse PFTs at 3 and 6 months.…”
Section: Blood and Blood Product Transfusionsmentioning
confidence: 99%